Study Torsion Capacity of Epoxy -Glass Fiber Composites - Noori, F T Mohammed; Jafar, H I; Abas, N A (Al-Nahrain Journal of Science, 2011)
In this study, torsion test was performed in order to examine the mechanical behaviors of epoxy and an epoxy reinforced by two types of glass fibers (chopped and yarn) composite rod. The stress-strain curves were constituted and examined in order to show the elastic and plastic regions, the yield point was 23.226o and 34.837o angle of twist for epoxy and epoxy /fibers respectively which is the same for both chopped and yarn glass fibers epoxy, from this test it was found that the epoxy rod initially yielded first, the cracks propagation in composite rod along the fibers direction, which caused eventually the delimitation of composite chopped and yarn glass fibers from the epoxy matrix. Then the white regions appear in composite rod and finally the fiber breakage and the catastrophic failure took place.